THE LAST TIME ANALYSIS OF THE FOLLOWING FAMILY IN AL-QUR'AN PERSPECTIVE - Rahmah, Rona Dwi (http://jagadalimussirry.com/, 2020)
Abstract. Earthquakes are natural disasters caused by shocks on the earth due to faults and the sudden movement of tectonic rocks that make up the earth's crust. This study of earthquakes will be interesting if explored further from the perspective of the Qur'an because in the Qur'an there are many verses that speak of earthquakes. As explained in the Qur'an Al-Zalzalah verses 1-8. On February 14 2016 to February 23 2016 aftershocks occurred in the Klagon Village Area, Saradan District, Madiun. To analyze when the end of aftershocks ends by using the Least Square Method and the relationship of frequency of aftershocks to times that include the Omori, Omogi 1, Omogi 2 and Utsu methods. The conclusion of this study is the Omogi 2 method which has obtained the correlation coefficient r = 0.195 from the correlation value -1 â‰¤ r â‰¤ 1, with the aftershocks ending on day 464 and from the comparison of aftershock frequency corresponding to the graph between the results data calculations with real data (actual data) namely the Omogi 2 method. And basically the term earthquake in the Qur'an can still be said not to make the verses interpreted as a single word containing the meaning of the earthquake as a brief explanation of aftershocks in the perspective of the Qur'an.